2008
DOI: 10.1038/sj.embor.7401152
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐cycle‐dependent binding kinetics for the early endosomal tethering factor EEA1

Abstract: Early endosomal antigen 1 (EEA1) is a cytosolic protein that specifically binds to early endosomal membranes where it has a crucial role in the tethering process leading to homotypic endosome fusion. Green fluorescent protein-tagged EEA1 (EEA1-GFP) was bound to the endosomal membrane throughout the cell cycle, and measurements using fluorescent recovery after photobleaching showed two fractions: one rapidly exchanging with the cytosolic pool, and the other with a long half-life. The exchange consists of a rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Rab5-EGFP and Rab7a-EGFP was supplied by Cecilia Bucci,39 Rab5wt in pMEP4 has been described previously. 27 Cell lines …”
Section: Methods Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rab5-EGFP and Rab7a-EGFP was supplied by Cecilia Bucci,39 Rab5wt in pMEP4 has been described previously. 27 Cell lines …”
Section: Methods Constructsmentioning
confidence: 99%
“…In order to assess endosomal maturation in a comparable system, we examined cells overexpressing Rab5wt, which causes an increase in endosomal size 23,26 similar to that induced by Ii. 27 Human fibroblasts expressing HLA-DR were transfected with Rab5wt or Ii and Rab5-GFP, and incubated with fluorescently labeled antibodies targeting mature HLA DR and lysotracker red, which accumulates in compartments with a low pH. Remarkably, the presence of Rab5GFP on Ii-induced endosomes persisted for extended periods, with an average residence of Rab5GFP on the endosomal membrane of 2½ h in human fibroblasts (Figure 6a and quantified in Figure 6c).…”
Section: Endosomal Maturation Is Delayed In Cells Expressing IImentioning
confidence: 99%
“…The cytosolic tail of Ii is fusogenic and expression of Ii causes a prolonged endosomal pathway and enlargement of early endosomes (Engering et al, 1998;Nordeng et al, 2002;Romagnoli et al, 1993;Stang and Bakke, 1997). High-level expression of Rab5 has been found to increase endosome recruitment of EEA1 and enhance the early endosome fusion, resulting in larger endosomes (Bergeland et al, 2008;Gorvel et al, 1991;Li et al, 1995;Simonsen et al, 1998;Stenmark et al, 1994). cDNA for both molecules was subcloned into the inducible expression vector, pMep4, and as a reporter for the early endosomes we used the C-terminus of EEA1 (residues 1257-1411) fused to GFP (ctEEA1-GFP) (Bergeland et al, 2008;McBride et al, 1999).…”
Section: Rapid Fusion Of Enlarged Early Endosomesmentioning
confidence: 99%
“…High-level expression of Rab5 has been found to increase endosome recruitment of EEA1 and enhance the early endosome fusion, resulting in larger endosomes (Bergeland et al, 2008;Gorvel et al, 1991;Li et al, 1995;Simonsen et al, 1998;Stenmark et al, 1994). cDNA for both molecules was subcloned into the inducible expression vector, pMep4, and as a reporter for the early endosomes we used the C-terminus of EEA1 (residues 1257-1411) fused to GFP (ctEEA1-GFP) (Bergeland et al, 2008;McBride et al, 1999). All constructs were stably transfected into Madine-Darby canine kidney cells (MDCK) and human fibroblasts (M1 cells).…”
Section: Rapid Fusion Of Enlarged Early Endosomesmentioning
confidence: 99%
“…Recent report has demonstrated that the binding kinetics of EEA1 to the endosomal membrane can be separated into 2 fractions: one rapidly exchanging with cytosolic pool, and the other is the immobile fraction. 26 Interestingly, it has been shown that during mitosis, the dissociation rate of EEA1 from early endosomes is accelerated, and the immobile fraction is reduced. 26 The Ser 459-phsophrylated form of vimentin may associate with a protein(s) that alters the binding kinetics of EEA1 to the early endosomes during mitosis.…”
Section: Discussionmentioning
confidence: 99%